Book Reviews. Issue 1 (1st March 2022) - Unknown
Abstract : Brandon Farnsworth, Anna Jakobsson, and Vanessa Massera, eds. 2021. Taking the Temperature: Crisis, Curating, and Musical Diversity, 2nd edition. Zurich: OnCurating.org. Eckersall, Peter, and Bertie Ferdman. 2021. Curating Dramaturgies: How Dramaturgy and Curating are Intersecting in the Contemporary Arts . New York: Routledge, 201 pp., Ebook available.